Optimization of Micro-Texture Parameters for Machine Tool Guide Rail Combination Based on Response Surface Methodology and Research on Its Anti-Friction and Lubrication Performance - Youzheng Cui; Bingyang Yan; Minli Zheng; Haijing Mu; Chengxin Liu; Dongyang Wang; Xinmiao Li; Qingwei Li; Hui Jiang; Fengjuan Wang; Qingming Hu (Lubricants, 2025)
In the process of heavy-duty cutting, the reciprocating motion of the sliding guide pair surface is prone to local wear, which seriously affects the overall machining accuracy and service life of the machine tool. This study proposes a biomimetic micro-texture design scheme combining elliptical grooves and shell-shaped grooves on the surface of carp as biomimetic prototypes to enhance the oil film bearing capacity, drag reduction, and wear resistance of guide rail pairs. Based on Fluent fluid simulation research, it has been shown that this texture has a better dynamic pressure lubrication effect. We used response surface methodology to optimize the texture design parameters and further verify the accuracy of the optimal parameters with the NSGA-II genetic algorithm. The results show that under lubricated conditions, the load-bearing pressure of the combined micro-textured guide rail pair increased by 53.79%, the friction coefficient decreased by 39.04%, and the temperature decreased by 15.83%. This texture can still significantly improve drag reduction and wear resistance in a low-oil state.